مساهمة في دراسة التأثير البيوكيميائي (الأليللوباثي) لعشبة حليبة الشواطئ (L. Euphorbia paralias) في إنبات ونمو بادرات بعض النباتات العشبية . - حداد دينا; طباش سمير (Latakia University Journal -Biological Sciences Series, 2018)
تم إجراء تجارب مخبرية لدراسة تأثير المستخلص المائي للمجموع الخضري لعشبة حليبة الشواطئ Euphorbia paralias، وبتراكيز مختلفة (2%،4%،8%) في إنبات ونمو الرشاد ((Lepidium sativum، الخس(Lactuca sativa)، البقلة ((Portulaca olerace.أظهرت النتائج زيادة متوسط إنبات بذور البقلة بنسبة وصلت إلى 7%، بينما لم يظهر تأثير ملحوظ للمستخلص في إنبات بذور الرشاد، وقد خفض المستخلص إنبات بذور الخس بنسبة35,9 % عند التركيز 8% . بالمقابل كان تأثير المستخلص منشطاً لطول سويقات عشبتي البقلة والرشاد ونبات الخس وعند جميع التراكيز المستخدمة، وكانت أعلى نسبة تنشيط لسويقات الرشاد عند التركيز 2% بنسبة 58,2 %، أما بالنسبة للجذير يلاحظ وجود تأثير مثبط لنبات البقلة و الخس عند التركيز 2% ومنشطاً لعشبة الرشاد، ثم أصبح التأثير مثبطاً عند التركيزين 4% و8% لنباتات الاختبار الثلاث، وكانت عشبة البقلة الأكثر حساسية وتأثراً إذ انخفض طول الجذير بنسبة 53,38 % عند التركيز 4%، و بنسبة 72% عند التركيز 8% وانخفض طول الجذير عند الرشاد و الخس بنسبة 25,82 % و34,95 % بالنسبة للشاهد على التوالي، ويعزى التثبيط الى مركبات التضاد الحيوي الأليلوباثي الموجودة في المستخلص المائي لعشبة حليبة الشواطئ مما يؤثر سلباً في نباتات الاختبار، يمكن الاستفادة من مستخلصات عشبة حليبة الشواطئ ، كمثبطات لنمو بعض الأعشاب الضارة بعد إجراء المزيد من التجارب. Laboratory experiments were conducted to study the effect of the aqueou extract of the vegetative parts of the Euphorbia paralias at different concentrations (2%,4%,8%) in seed germination and seeding growth of the Lepidium sativum, Lactuca sativa and Portulaca oleracea. The results indicated increase in germination ratio of Portulaca oleracea. up to 7%. while the effect of the extract was not evident in the germination of the seeds of Lepidium sativum, and decreased the germination ratio of Lactuca sativa seeds by 35.9% at the concentration of 8%.In contrast, the extracts stimulated the length of the stalks of Portulaca oleracea , Lepidium sativum and Lactuca sativa plants at all used concentrations used. The highest rate of stimulated stalks legnth of Lepidium sativum at 2% was 58.2%. inhibitory effect of water extract observed for root length of Portulaca oleracea and Lactuca sativa plants at 2% , and stimulation effect pour Lepidium sativum, The effect became evident at the concentrations of 4% and 8% for the three plants. The most sensitive and affected plants was Portulaca oleracea, where the length of the root decreased by 53.38% at the concentration of 4% and by 72% at the concentration of 8% ,while the length of the root Lepidium sativum and Lactuca sativa decreased by 25.82% and 34.95% was decreased for 4% and 8%respectively. The results suggested that this weed may affect seedling growth, due to inhibitory or stimulatory effect of Allelochemicals , which present in water extract of this weed . and may used as potential Bioherbicide after further experiments